Encouraging learning : how you can help children learn - Nottingham, James (London ; New York : Routledge, 2013)
"In this inspiring, humorous, and practical book he shows what you can do to help children of all ages develop into confident, thoughtful and independent learners. Based around the acronym ASK, this book explores attitudes, skills and knowledge to learning - what is required and how to develop these skills more effectively. It shows how to encourage independent thinking and a spirit of inquiry in your children. Highlights include: - The dangers of calling our children clever, bright and gifted; - The best ways to teach wisdom; - How to help children excel in exams; - Why curiosity did not kill the cat. With a foreword written by John Hattie, Encouraging Learning draws on research from some of the most respected experts on thinking and learning to identify the best ways to help children learn more effectively, efficiently and co-operatively. For everyone living or working with children - particularly teachers, parents, carers and youth workers - this book shows you some of the best ways to enhance children's learning, including how to question, praise, and encourage more effectively"--
"David Fulton book"--Cover.
Includes bibliographical references.
Description based on metadata supplied by the publisher and other sources.
Electronic reproduction. Santa Fe, Arg.: elibro, 2020. Available via World Wide Web. Access may be limited to eLibro affiliated libraries.
Keywords: Motivation in education; Electronic books